Functional modeling of carbon nanotubes synthesis control - V. V. Burlyaev; E. V. Burlyaeva; A. I. Nikolaev; V. B. Peshnev; S. V. Razlivinskaya (Тонкие химические технологии)
We discover and formalize the relations between set properties of the material and its synthesis conditions. We provide a formal description of carbon nanotubes synthesis control by means of functional modeling. The result is the hierarchical structure visual description that is the set of related diagrams. The diagrams describe the technological and control processes of carbon nanotubes synthesis and its relations including feedbacks.